A study of some chemical characteristics of the marshes of southern Iraq for the year 2015 A Comparative Study of Al-Chibayish Marshes in (Dhi Qar) and (Al-Mashab and Al-Salal) Marshes in Basra Governorate (Journal of the College of Basic Education, 2022)
The research studied and comparative of some of the chemical characteristics of Chabaish marsh in the province (Dhi Qar) and (Almshab and Alsalal) marshes in the province of Basra in 2015, and through the analysis of the results of the characteristics it had been found that the a variation during the seasons, where the acid function had taken by the baseband side, which is a prevalent trait for the Iraqi waters in general, it is also include within the environmental determinants for the purpose of irrigation, drinking and consumption by animals, but for melted oxygen it was part of the environmental determinants for the purpose of drinking, except for the summer to Chabaish marsh, and in the autumn for the (Almshab and Alsalal) marshes are the higher in term of the environmental determinants and the total salts amounts outside environmental determinants for the purpose of drinking, but for the purpose of animal consumption it had fluctuated between good and allowed to be used, throughout the electrical conductivity results it had noted that it is outside environmental determinants for the purpose of drinking and irrigation, water when used for irrigation (dangerous salinity) to Chabaish marsh and(Almshab and Alsalal) marshes for the year 2015 it had noted that it is within the class (C5), which is unfit for irrigation water, except for the fall season of the (Almshab and Alsalal) marshes which are within the class (C4), which is very high salinity water and not suitable for irrigation except crops of high endurance of salinity. soils need continuous broach operations and huge care , Nitrate and Phosphate ratios recorded values within the environmental determinants for the purpose of drinking, while the Magnesium was out of environmental determinants for the purpose of drinking and their value categorized within the limits of (good and very good), except in the winter the marsh was within the limits (allowed to use them) for animal consumption.